Sekolah Lapang Program: Fostering Environmental Awareness Character Through Sustainable Education Approach - Rediani, Ni Nyoman; Hallatu, Trinovianto G.R; Palittin , Ivylentine Datu; Retnaningtyas, Hanova Rani E.; Nainggolan, Herrio Tekdi; Sunarni; Witdarko, Yus (Universitas Pendidikan Ganesha, 2024)
The lack of environmental awareness and concern among school-age children poses a challenge in fostering environmentally responsible character from an early age. This study aims to analyze the impact of the Sekolah Lapang program on students' environmental awareness. Specifically, it seeks to measure changes in attitudes before and after participating in the program and to evaluate its effectiveness in cultivating environmental consciousness among children. This study employs a quasi-experimental method with a pretest-posttest design. Data were collected using a questionnaire consisting of 20 statements measuring students' environmental awareness. Data analysis was conducted using descriptive techniques to identify general trends and inferential analysis using a t-test to examine significant differences before and after the intervention. The findings indicate that the Sekolah Lapang program significantly enhances students' environmental responsibility. The average score increased by 16.85 points, with the t-test results showing a significance value of 0.00 (p < 0.05), indicating a statistically significant change. These findings confirm that the Sekolah Lapang program is an effective strategy for instilling environmental awareness in school-age children and can serve as a sustainable environmental education model.